Metformin Inhibits Follicle-Stimulating Hormone (FSH) Action in Human Granulosa Cells: Relevance to Polycystic Ovary Syndrome - Rice, Suman (Endocrine Society, 2013)
BACKGROUND: Women with anovulatory polycystic ovary syndrome (PCOS) are generally insulin-resistant and as a consequence are often treated with the biguanide metformin. Results with metformin have, however, been variable with some studies demonstrating induction of regular cycles and an increase in ovulation, whereas others do not. Hence more understanding is needed regarding the mechanism of metformin's actions in ovarian granulosa cells especially in light of previous demonstrations of direct actions. OBJECTIVE: The aim of this study was to investigate metformin's interaction with the FSH/cAMP/protein kinase A pathway, which is the primary signaling pathway controlling CYP19A1 (aromatase) expression in the ovary. METHODS: The effect of metformin on FSH and forskolin-stimulated aromatase expression in human granulosa cells was measured by quantitative real-time PCR. Activity was assessed after transfection with a promoter II-luciferase construct, and by an RIA measuring conversion of androgen to estrogens. The effect on FSH receptor (FSHR) mRNA was assessed by quantitative PCR. Levels of phosphorylated cAMP response element binding protein (CREB) and CREB-regulated transcription coactivator 2 (CRTC2) were measured by Western blotting and cAMP by a bioluminescent assay. RESULTS: Metformin markedly reduced FSH but not forskolin-stimulated aromatase expression and activity. This effect was exerted by inhibition of basal and ligand-induced up-regulation of FSHR expression. Metformin also reduced FSH-induced phosphorylation of CREB and hence CRE activity, which could potentially disrupt the CREB–CREB-binding protein–CRTC2 coactivator complex that binds to CRE in promoter II of the aromatase gene. This is mediated in an AMP-activated protein kinase-independent manner, and does not involve alteration of cAMP levels. CONCLUSION: These finding have implications for the use of metformin in the treatment of anovulation in women with PCOS.